Evaluation of graft uptake using temporalis fascia and cartilage perichondrium supplemented with autologous platelet rich plasma in tympanoplasty - Ankle, N. R.; Havaldar, Rajesh Radhakrishna; Sinha, Sweta (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Tympanoplasty involves grafting the perforation of the tympanic membrane with materials such as temporalis fascia, cartilage perichondrium, periosteum, vein, fat etc. Both temporalis fascia and cartilage perichondrium are easy to harvest with minimum donor site complications and both have been used extensively in tympanoplasty. Platelet rich plasma aids as an adhesive and supplements healing by providing growth factors. Till date there is scarcity of literature comparing the healing outcome of both cartilage perichondrium and temporalis fascia supplemented with platelet rich plasma. Hence, in this study we are comparing cartilage perichondrium supplemented with platelet rich plasma and temporalis fascia supplemented with platelet rich plasma. Methods: An observational study involving 60 patients was done. Patients with chronic otitis media were evaluated by otoendoscopy to assess the ear and were categorised into 2 groups which received temporalis fascia and cartilage perichondrium respectively. All cases were supplemented with platelet rich plasma. Post-operative assessment was done by otoendoscopy. Results: Total 21 patients received temporalis fascia and 39 patients received cartilage perichondrium. At the end of 6 weeks the graft site appeared unhealthy in 6.66% cases who received temporalis fascia and 1.66% in those who received cartilage perichondrium. Conclusions: We found that cartilage perichondrium supplemented with platelet rich plasma had a better uptake after 6 weeks due to its superior mechanical stability. The results are more rewarding than the use of temporalis fascia with platelet rich plasma.